THE ROLE OF ISLAMIC EDUCATION IN OVERCOMING BULLYING IN INDONESIA - Zaharuddin M, Zaharuddin M; M. Imamuddin, M. Imamuddin; Hadini, Hadini; Nurbayani, Nurbayani; Hayati, Hayati (LP2M IAI Al-Khairat Pamekasan, 2025)
School is a formal institution of education that functions to prepare or make its students become a person as well as a citizen with integrity. In addition, schools are also expected to be able to provide protection, direction, and supervision for children who are preparing for their lives later. But in reality there are still many students who have not achieved this development, this happens because there are still several problems that arise in the school environment, one of the significant phenomena is bullying. The phenomenon of bullying behavior in Indonesian educational institutions has become the main focus in various previous literatures, including: First, Yuyarti: Overcoming Bullying Through Character Education, in this study, the researcher focuses on the role of Islamic education in overcoming bullying. The expected purpose of this study is to formulate the contribution of Islamic education in overcoming bullying. This research uses a research method using an approach or a library research method. Islamic education is present as a solution in overcoming bullying that occurs in educational institutions by realizing the following steps: 1. The Active Role of Educators: a. Giving Advice, b. Guidance on Worship Practices, c. Supervision, d. Collaboration with Parents, 2. Actualization of Religious Moderation Materials, 3. Holding Anti-Bully Socialization, 4. Peer Education Program. For educational institutions to be able to implement these steps in overcoming and anticipating bullying.